Analysis of heavy metals content in commercial, medicated and herbal toothpaste - Bojanić, Ljubica; Jelić, Dijana; Djermanović, Mirjana; Umićević, Nina (Archives of Pharmacy, 2022)
The toothpastes are personal care products that are used on daily regular basis for oral hygiene. They come in different form, such as liquid, paste, gels, powder…If used as prevention for dental cavities or some other oral health issues they are categorized as OTC anticaries products. Therefore it is very important to have information on their safety. When it comes to quality control fluoride content which is an active ingredient in toothpaste, physicochemical properties, including microbiological ones are very important. Special attention is also given to assessment of heavy metals, a micropollutants which might be toxic and prone to bioaccumulation. The presented research presents the analysis on heavy metals content (Pb, Cu and Ni) in eleven toothpaste classified as general (commercial), medicated and herbal. As an analytical methods atomic absorption spectrophotometry was used according to Regulations on safety of consumer goods, official Gazette of the Republic of Srpska, No 17/15, Act 27. The results showed that copper and nickel were in allowable concentration, but the lead concentration in some investigated samples was increased. Taking into consideration that heavy metal excess presence can have potential adverse effects on health and the environment, constant survey and research is significant. Moreover, since toothpaste are applied on a daily basis and directy into the mouth in which toxin can be absorbed rather quickly through the mucosa membrane and later into the bloodstream, the product safety is inevitable.